1986
DOI: 10.1021/i300022a028
|View full text |Cite
|
Sign up to set email alerts
|

Cure and photodegradation of two-package acrylic/urethane coatings

Abstract: Ind. Eng. Chem. Prod. Res. Dev. 1986, 25, 289-296 289 of composites fabricated with resin-treated coir fiber mat showed an posites based on untreated coir fiber mat a significant reduction in ILSS was observed ( Figure 11).It may be concluded from these studies that a coating of USP resin on coir fibers improves the compatibility of Kulkarnl, A. G.; Cheriyan, K. A.; Satyanarayana, K. G.; Rohatgi, P. K. J. Appl. folym. Scl. 1983, 28, 625. Mukherjee, R. N.; Pal, S. K.; Sanyal, S. K.; Sanyal, S. K. J. Appl. po/ym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 12 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…1 shows the IR spectrum of the acrylic-urethane from before ageing to 2700 h of photo-oxidation in artificial accelerated ageing. The initial spectrum and the main band assignments have already been discussed in previous papers [17,18]. Fig.…”
Section: Photo-ageing Of Unstabilised Acrylic-urethane (Sample A)mentioning
confidence: 96%
“…1 shows the IR spectrum of the acrylic-urethane from before ageing to 2700 h of photo-oxidation in artificial accelerated ageing. The initial spectrum and the main band assignments have already been discussed in previous papers [17,18]. Fig.…”
Section: Photo-ageing Of Unstabilised Acrylic-urethane (Sample A)mentioning
confidence: 96%
“…In previous studies of acrylic urethane photodegradation under harsh exposure conditions, it was found that the addition of TIN 770 reduced the rate of both cross-link scission and carbonyl growth (Bauer et al, 1986(Bauer et al, , 1988. The photooxidation rate remained constant over the exposure time.…”
Section: Hals Stabilizationmentioning
confidence: 84%
“…Support for the participation of peracid species in coating oxidation is found in model compound studies by Felder et al (1980). IR and NMR studies of coating degradation chemistry reveal substantial differences between urethane and melamine cross-linked coatings containing Tinuvin 770 (Bauer et al, 1986). This additive is both more effective and more persistent in urethane coatings than in melamine coatings.…”
Section: Discussionmentioning
confidence: 98%